Processo judicial eletrônico : reflexão crítica acerca da garantia fundamental de acesso à justiça do trabalho - Carvalho , George Barbosa Jales de (2015)
Modern society increasingly technological, has undergone constant change, whose effects reach the science of law. Gradually, the use of technology is implemented within procedural law, in order to facilitate access and expedite proceedings. From this perspective, it was up to the courts to implement new technologies that made proceedings faster and more effective. Thus came the electronic process, which was not restricted only to transport the records from paper to the virtual environment (formal aspect). It went further, there was a change in material aspects, influencing the application of procedural principles, and the very essence of judicial process. The labor proceedings was no different. With the introduction of PJe-JT, it was possible to perceive significant changes in the dynamic of proceedings, especially relative to access to the labor courts, through the justice postulandi.In this sense, it is relevant the discussion and reflection on the impact of the PJe-JT in the labor process, especially with regard to the violation of the principle of wide access to justice, constitutionally guaranteed in section XXXV, article 5 of the Federal Constitution 1988. This research seeks, through the deductive method, from the confrontation between the introduction of the PJe-JT and the principle of access to justice, specifically in regards to the use by the claimants of jus postulandi; demonstrate that the new electronical procedural systematic has proven to some extent, violator of the principle of access to fair legal system. To that extent, it was not only found the elimination of the possibility of using jus postulandi, as were also suggested ways that can be adopted to prevent or compensate for the extinction of this important institute.